An ordinary gift The work of art as theological conversation - Mallaby, Anne; Byrne, Libby (2017)
This case study considers the nature of making, seeing and being with art in a dialogue about the experience of Libby Byrne's exhibition, 'An Ordinary Gift' in Melbourne, 2016. The article explores the nature of making, seeing and being with art as a methodological framework for theological inquiry. Bringing to bear their experiences as artist and curator, two researchers examine recorded viewers' responses to the exhibition, as a means of understanding the nature of theological engagement and insight that was possible in the process of making, being with and seeing this public exhibition. The article acknowledges that the work of art offers an ordinary gift of containment for the ineffable qualities of our lived experience with God. A faith-ful framework of communal engagement can therefore offer an external reference point that guides and shapes the making, the seeing and even the ways in which we are able to be with art. As we transform the way we engage with theological questions and concerns we are in turn transformed by the ordinary gift of making, seeing and being with art.
Keywords: aesthetic theology; Art; Exhibition; practice-led; Seeing